Hospital Base Cross Sectional Study of Traditional Medical and Daily Care Practice and Attitude Among Pediatric Caregiver in Tertiary Hospitals in Sana'a, Yemen (2025-2026) - Abualrejal, Ashwaq Abdullah; Alezi, Hajer Hassan; Alfakih, Maria Mahmood; Aljabwobi, Roa'a Sharyan Sharyan (My University, 2026)
Background: Traditional medical and daily care practices remain widely used in many low- and middle-income countries, including Yemen, where cultural beliefs, limited healthcare access, and socioeconomic challenges strongly influence caregivers' health-seeking behaviors. Some of these practices may delay appropriate medical care or expose children to preventable complications. However, there is limited published data in Yemen regarding the prevalence and attitudes toward traditional pediatric care practices. Objective: To assess the prevalence patterns, attitudes, and associated sociodemographic factors related to traditional medical and daily care practices among pediatric caregivers attending tertiary hospitals in Sana'a, Yemen.